Revisiting the link between output growth and volatility: panel GARCH analysis - DENİZ, PINAR (PHYSICA-VERLAG GMBH & CO, 2021)
This paper explores the link between output growth and volatility using several macroeconomic variables for a panel of countries for the period of 1971-2014. Using an augmented panel GARCH-M model, we allow for the first time in the literature for independent variables to be part of the conditional equations. The paper is also novel in terms of encompassing an extensive number of countries and country groups. The relationship between output growth and volatility is observed to vary between different country groups. Empirical findings regarding the effect of exogeneous variables suggest that trade openness contributes to economic growth and institutional quality lowers economic volatility.
Keywords: Growth; Volatility; Panel GARCH-M model; ECONOMIC-GROWTH; CROSS-COUNTRY; UNCERTAINTY; INSTITUTIONS; INFLATION; TRADE; VARIABILITY; OPENNESS; REAL; INTEGRATION